Development of microsatellite markers for the house cricket, Acheta domesticus (Orthoptera: Gryllidae) - Yash Munnalal Gupta; SUPATCHAREE TANASARNPAIBOON; KITTISAK BUDDHACHAT; SURIN PEYACHOKNAGUL; PHATTHARAPORN INTHIM; SOMJIT HOMCHAN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Gupta YM, Tanasarnpaiboon S, Buddhachat K, Peyachoknagul S, Inthim P, Homchan S. 2020. Development of microsatellite markers for the house cricket, Acheta domesticus (Orthoptera: Gryllidae). Biodiversitas 21: 4094-4099. The house cricket, Acheta domesticus, is one of the species of crickets commonly found in Thailand. Insect breeders in Thailand prefer to breed house cricket as food due to its better taste and popularity among local people. Moreover, largescale breeding industries also breed house cricket to produce cricket-based edible products. Insect breeding industry is growing rapidly and requires primary precaution for sustainable production. To facilitate breeding system to maintain genetic variation in the captive population, we have sequenced the whole genome of A. domesticus to search for simple sequence repeats (SSRs) in order to develop polymorphic microsatellite markers for preliminary population genetic analysis. A total of 112,157 SSRs with primer pairs were identified in our analysis.  Of these, 91 were randomly selected to check for amplification of microsatellite polymorphisms. From these, nine microsatellites were used to check genetic variation in forty-five individuals of A. domesticus from the Phitsanulok population (Thailand).  These microsatellite markers also showed cross-amplification with other three species of edible crickets, specifically Gryllus bimaculatus, Gryllus testaceus, and Brachytrupes portentosus. The microsatellite markers presented herein will facilitate future population genetic analysis of A. domesticus populations. Moreover, the transferability of these makers would also enable researchers to conduct genetic studies for other closely related species.